(untitled) (Archives of Mechanics - Test, 2010)
Quasi-static simulations of a concrete behaviour with steel fibres under uniaxial tension were carried out using a discrete irregular lattice model. Fibrous concrete was described at a meso-scale as a three-phase material composed of aggregate, cement matrix, steel fibres and interfacial zones between cement matrix and aggregate, and between cement matrix and steel fibres. The effect of the fibre interface strength, fibre volume, fibre orientation, fibre length and specimen size on the concrete behaviour was investigated. The results of two- and three-dimensional analyses were compared.